When politicians switch parties: Rewarded by voters or punished at the polls? - Thygesen, Frederik; Jensen, Jens Høyer (Politica, 2025)
Do voters penalize elected municipal politicians who switch parties during a term? Using election data from Danish municipal elections between 2009 and 2021, this article shows that party switchers are penalized by 0.33 percentage points fewer votes in the subsequent election. In an average municipality with 30,000 eligible voters, this corresponds to approximately 100 personal votes. The study further finds that opportunistic switchers are penalized more harshly than idealistic ones, and early switchers are penalized more than late switchers. The results indicate that party switching has significant costs for politicians and affects voter trust and support.